Powdery Mildew of Cucurbits in Florida - Hector G. Nuñez-Palenius; Donald Hopkins; Daniel J. Cantliffe (EDIS, 2006)
HS-1067, a 9-page illustrated fact sheet by Hector G. Nunez-Palenius, Donald Hopkins and Daniel J. Cantliffe, describes this serious disease of cucurbit crops in Florida, the symptoms and disease development, environmental factors, management, the use of plants with genetic resistance, management using fungicides for susceptible cultivars, the use of biorational and non-harmful chemicals, and biological fungicides. Includes references and tables of powdery mildew resistant or tolerant cultivars of cucumber, melon, and squash. Original publication date June, 2006.